Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 3740 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Larrea tridentata (DC.) Coville" ] } The dataset includes 3740 records from 85 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0058385-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences